Modeling the training in the volley game, by softwear programs - Cojocaru, A.-M.; Cojocaru, M. (Science, Movement & Health, 2018)
Problem: The electronic computer or computer has become an indispensable and extremely efficient and convenient tool for those who work in great performance due to their high ability to record and store information and, especially, processing capabilities, extremely fast and from countless points of view. Purpose: With a more sophisticated "soft", values of individual behaviors can be recorded and can be calculated for each exercise used in the training, the number of ballots, the number of balls actions, successes and mistakes, by calculating some indices efficiency of actions. The premises of the study: In this paper we start from the idea of trying to concentrate as many ways of evaluating the training and contest in the volleyball game. We also want to achieve a systematization of assessment tools so that we can support teachers and coaches working in the field. Methods of research. As a working method I used: bibliographic documentation; interpretation of statistical and mathematical method; graphical representation method. Discussions: In the current practice, there is no match, without the opponents, not to study with each other, with a great deal of detail, from a tactical point of view. Tactical game plans are thoroughly prepared, applied and seriously analyzed. Conclusions: The mathematical optimization of the evaluation of tactical action in volleyball play may be the starting point for accurate and accurate interpretation of the value of the action. The use of multimedia tools in the preparation of a volleyball team is a starting point for the realization of a vision-calculator configuration by designing, selecting and checking the tools and working methodology.